2008
DOI: 10.1021/jp806606h
|View full text |Cite
|
Sign up to set email alerts
|

Organic Dyes Containing a Cyanovinyl Entity in the Spacer for Solar Cells Applications

Abstract: Series of dyes containing a cyanovinyl entity in the spacer have been developed and characterized. Dye-sensitized solar cells (DSSCs) using the dyes as the sensitizers exhibited good efficiencies ranging from 3.48−4.92%, which reached 45−70% with respect to that of an N719-based device fabricated under similar conditions. In general, better DSSC performances are observed with molecules having a shorter distance between the internal cyanovinyl entity and the amine donor. Computational analysis indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 62 publications
2
56
0
Order By: Relevance
“…A similar trend was also observed in dipolar compounds containing an internal cyanovinyl unit that we reported recently. [21] Further elongation of the conjugated spacer between the thiophene and the peripheral arylamine leads to slightly hypsochromatic shift of the absorption band in 8 and 9. Compound 3 probably has greater charge separation in the excited state in view of its longest absorption and emission (vide infra) wavelengths among all these compounds.…”
Section: Synthetic Strategymentioning
confidence: 99%
“…A similar trend was also observed in dipolar compounds containing an internal cyanovinyl unit that we reported recently. [21] Further elongation of the conjugated spacer between the thiophene and the peripheral arylamine leads to slightly hypsochromatic shift of the absorption band in 8 and 9. Compound 3 probably has greater charge separation in the excited state in view of its longest absorption and emission (vide infra) wavelengths among all these compounds.…”
Section: Synthetic Strategymentioning
confidence: 99%
“…In most of the organic dyes the donor segment is typically an aromatic amine such as carbazole [10], phenothiazine [11], triphenylamine [12], phenoxazine [13], indoline [14] etc. It has been reported that the presence of electron accepting moieties such as diketeopyrrolopyrrole [15], benzotriazole [16], cyanovinyl [17], plays an active role of auxiliary acceptors and they serve as effective charge transporters between the donor and acceptor [18]. Typically, thiophene and its derivatives have been successfully utilized as p-conjugation bridges in the molecular design of organic dyes, due to their polarizability and overall stability [19].…”
Section: Introductionmentioning
confidence: 99%
“…The absorption band below 400 nm exhibited vibronic characteristics of anthracenyl entity for all dyes except An-3. The vibronic pattern may be buried under the intense absorption band due to bis(fluorenyl)amino moiety [18]. The λ max value of the ICT band decreases in the order of An-3 > An-4 > An-1 ≈ An-2.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Meanwhile, intermolecular dye aggregation and recombination of conduction-band electrons with triiodide present in the electrolyte have to be suppressed. In recent years, we have been interested in push-pull type metal-free sensitizers using arylamine as the electron donor and 2-cyanoacrylic acid as the electron acceptor [13][14][15][16][17][18][19][20][21]. In continuation of our studies on sensitizers, we became interested in dyes containing fused aromatic segments in the spacer based on the following reasons: (1) the rigid segment has less reorganization energy and may facilitate electron transfer; (2) rigid segments with a planar skeleton may reduce steric congestion and allow more compact dye packing on the TiO 2 surface.…”
Section: Open Accessmentioning
confidence: 99%